An Experimental and Analytical Study of the Flexural Capacity of reinforced Geopolymer Concrete Beams - Kumar, Anil; Mishra, Shambhu Sharan (Engineering, Technology & Applied Science Research, 2025)
This study investigates the flexural strength of reinforced Geopolymer Concrete (GPC) beams using experimental and analytical methods. Five sets of reinforced beams were cast, each containing three beams with dimension of 150 mm x 200 mm x 1200 mm. One set was made with conventional concrete, while the other sets were made with GPC with different percentages of reinforcement. In order to determine compressive strength, three cube samples of conventional and GPC were also cast. The experimental flexural capacity of the beams was evaluated using a four-point loading test. The analytical flexural capacity was predicted deploying the IS 456:2000 standard method for reinforced concrete beams. The findings revealed that the predicted flexural capacity was similar or lower than the experimental values for GPC beams. Therefore, the IS 456:2000 approach can be utilized to predict the flexural capacity of reinforced GPC beams.